Long-term phosphorus removal in land treatment systems: Evaluation, experiences, and opportunities. Issue 5 (4th March 2017) - Seguí, Maria del Mar Batista; Hess, Tim; Sakrabani, Ruben; Tyrrel, Sean
ABSTRACT: Excessive release of phosphorus (P) from urban wastewater into water bodies is a significant environmental concern. Land treatment systems (LTS) have been used for the last 150 years as a low-cost and low-energy tertiary wastewater treatment. However, their P removal capacity is limited by soil adsorption capacity. Accurate P-removal lifespan prediction is needed to provide confidence in this technology and to support long-term wastewater treatment planning. This review outlines the history of LTS, describes the main P removal processes in soils, and critically analyzes the research methods used to date to assess long-term P removal in soil. Finally, an assessment is made of the role that modeling tools can play in aiding our understanding of P processes in LTS soils and in forecasting system longevity.